(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study examines the complex relationship between social intelligence, professional efficacy, and teaching effectiveness among teachers in the educational context of Kerala, India. The study employs a blend of qualitative and quantitative techniques to comprehend the subordination of implementation to social intelligence. The results show a significant mediation effect, providing strong evidence that teachers’ social skills have a direct effect on their overall effectiveness in the classroom. In addition, the study highlights the outstanding importance of professionalism in predicting instructional success and the value of confidence in teachers' abilities. The findings hold important implications for teacher training programs, professional development programs, and education programs in Kerala. Social intelligence development is believed to be essential to improving educational practices. This study offers useful insights that may be used to improve programs that are targeted at improving education in the area, especially with teachers who work outside the borders of their profession.